1946
DOI: 10.1172/jci101682
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Shock Due to Salt Depletion; Comparison of the Hemodynamic Effects of Isotonic Saline, of Hypertonic Saline, and of Isotonic Glucose Solutions 12

Abstract: In the preceding paper, the peripheral vascular collapse induced in untraumatized dogs by the removal of sodium chloride has been described (1). In its effects on plasma volume, plasma protein, blood pressure, cardiac output, and circulation rate this type of peripheral vascular collapse is indistinguishable from that observed in traumatic shock. Depletion of water without salt, on the other hand, depresses the circulation much less severely. The reasons for this are not clear. The present experiments seek fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

1946
1946
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…experiments with salt depletion which were similar in every respect to these 8 save for the omission of this initial cardiac output measurement. Data from some of these incomplete experiments are given in tabular form in the subsequent paper (22) and have been used along with the data of Table I in the construction of Figures 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…experiments with salt depletion which were similar in every respect to these 8 save for the omission of this initial cardiac output measurement. Data from some of these incomplete experiments are given in tabular form in the subsequent paper (22) and have been used along with the data of Table I in the construction of Figures 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…The body fluids of the dehydrated animals were hypertonic, while the salt- Columns B and C are taken from previously reported data (2). The changes shown were produced in animals already in salt depletion shock.…”
Section: Discussionmentioning
confidence: 99%
“…As sodium and chloride ions enter the intraperitoneal fluid, water moves into the cells in response to osmotic forces. Diminution of the volume of extracellular fluid and plasma, swelling of the cells, and generalized hypotonicity are the inevitable end results (1,2,3). Since these changes occur rapidly and almost simultaneously, it is difficult to ascribe the primary causative role in the circulatory collapse which ensues to any one factor.…”
mentioning
confidence: 99%
“…It has been shown that, within certain limits of time, shock produced by acute salt depletion can be completely, or almost completely, reversed by the simple replacement of the salt deficit with hypertonic solutions of saline (13). It has been found, however, that the use of colloid solutions together with replacement of salt provides a distinct margin of safety (14).…”
Section: Discussionmentioning
confidence: 99%